Probabilistics finite element analysis for double layer steel space truss - Ng, Choon How (2014)
In this thesis, a double layer steel space truss was analyzed by using Probabilistic Method with ANSYS program and validate by Finite Element Method with manual calculation. This analysis is to determine the behaviors of the double layer steel space truss. Besides that, it is also to study of the probabilistic response analysis and input sensitivities of the double layer steel space truss. Nowadays space truss is widely used in many types of construction that included stadium, shopping mall, tower, stage, roof structure and also home design. The difference texture of assembly will definitely beautify a building or a place. In this research structure a 4 x 4 x 0.5 meter for the length, width and height had been used, there have 4 supports at the bottom of the structure, and resist of a total of 16 point loads on the top of the structure. The circular hollow cross section was used for the horizontal member and diagonal member for the structure. A 275N/mm 2 of yield strength was choose for the steel space truss. The material and geometry of the space truss was satisfying for this research since it passes all the design criteria in designing for tensile, compression and also buckling. The ANSYS results show very good agreement with manual calculation results. From the results of simulation, we get to know the real behavior of the structure under the applied loads. From probabilistic analysis, we got the results of cumulative distribution function, histogram plot, sensitivity plot and simple history plot by 10000 times of simulation. In the simulation results, 5 inputs were assigned to get the probabilistic maximum deflection, axial stress and axial elastic strain. The 5 inputs are force, outer diameter of horizontal member, outer diameter of diagonal member, thickness of horizontal member and thickness of diagonal member. Results from ANSYS program indicated that the maximum deflection is 7.74mm, maximum axial stress is 141.16MPa, and maximum axial elastic strain is 0.6722E-03.